SCREENING OF LINSEED ( L.) GERMPLASM UNDER EPIPHYTOTIC CONDITIONS AGAINST POWDERY MILDEW AND WILT DISEASES (Journal of Plant Disease Sciences, 2025)
A set of 122 linseed germplasm accessions was evaluated for their resistance to powdery mildew and wilt diseases under epiphytotic conditions at the AICRP Linseed experimental block, College of Agriculture, Nagpur, during the cropping season of 2023–24. The objective of the study was to identify resistant sources for use in linseed breeding programs targeting disease resistance.Out of the 122 germplasm entries, nine accessions (23045, 24032, 24035, 24043, 24049, 24050, 24051, 25024, and 27025) exhibited a highly resistant response to powdery mildew. Furthermore, all entries were also tested under wilt sick plot conditions to evaluate their response to wilt disease. Among these, one entry (27042) showed a highly resistant reaction to wilt, while 12 entries (23054, 24031, 24036, 24041, 24042, 25021, 25023, 27021, 27025, 27030, 27033, and 27034) were categorized as resistant.The remaining accessions were classified as moderately susceptible, susceptible, or highly susceptible to one or both diseases.
Keywords: Linseed; Powdery mildew; Wilt; Screening